Covid-19: Oral manifestations, impact and lessons for the future - Pant, Bashu Dev (Orthodontic Journal of Nepal, 2020)
The coronavirus disease 2019 (COVID-19) is a respiratory infectious disease caused by severe acute respiratory syndrome coronavirus-2 (SARS-CoV-2). The SARS-CoV-2 is mainly transmitted through respiratory droplets and close contact. Most of the infected people present with fever, cough and difficulty in breathing; some develop severe pneumonia, renal and multi-organ failure and some may remain asymptomatic. It has halted the economy and many people have lost their job or reduce their income significantly across the globe. Orthodontic patients coming for the treatment are under fear of contracting disease therefore number of patients are decreased and orthodontic practitioners are also afraid of doing treatment because of fear of contracting disease so; it has direct negative effect on the economy of orthodontic practitioners. Large number of orthodontic patients are in need of orthodontic return-visits, all patients who come for orthodontic visits should be performed with preventive measures to control transmission COVID-19.